Functional imaging for assessing regional lung ventilation in preclinical and clinical research - Karmali, Dipan; Sowho, Mudiaga; Bose, Sonali; Pearce, Jackson; Tejwani, Vickram; Diamant, Zuzana; Yarlagadda, Keerthi; Ponce, Erick; Eikelis, Nina; Otvos, Tamas; Khan, Akram; Lester, Michael; et al. (Frontiers in Medicine, 2023)
Dynamic heterogeneity in lung ventilation is an important measure of pulmonary function and may be characteristic of early pulmonary disease. While standard indices like spirometry, body plethysmography, and blood gases have been utilized to assess lung function, they do not provide adequate information on regional ventilatory distribution nor function assessments of ventilation during the respiratory cycle. Emerging technologies such as quantitative CT, 4D CT, functional MRI and X-ray velocimetry can assess regional ventilation using non-invasive radiographic methods that may complement current methods of assessing lung function. As a supplement to current modalities of pulmonary function assessment, functional lung imaging has the potential to identify respiratory disease phenotypes with distinct natural histories. Moreover, these technologies may offer an optimal strategy to evaluate the effectiveness of novel therapies and therapies targeting localized lung tissue in preclinical and clinical research. In this review, we will discuss the features of functional lung imaging, as well as its potential application and limitations to adoption in research.